1974
DOI: 10.1085/jgp.63.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Control of Retinal Sensitivity

Abstract: Both the "on" and the "on-off" ganglion cells in the mudpuppy retina generate graded responses over a narrow range of log test intensities. Sustained full field or surround backgrounds change the range of center log test intensities that elicits the graded response for both cell types. The on-off, but not the on ganglion cells are further affected by moving or flashing surround backgrounds. These cells are hyperpolarized, threshold is elevated, and the entire graded range of response is elicited by a higher ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0

Year Published

1975
1975
2005
2005

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(61 citation statements)
references
References 25 publications
8
53
0
Order By: Relevance
“…The dynamic range was also narrower for this class of ganglion cell, and their responses to increments of illumination were larger than ganglion cells receiving TTX-insensitive input. This is in agreement with previous studies that have shown that the dynamic range of transient ganglion cells is narrower than that of sustained ganglion cells (Werblin and Copenhagen, 1974;Thibos and Werblin, 1978). The dynamic range of bipolar and ganglion cell responses to light has been attributed to GABA-mediated input from amacrine cells (Euler and Masland, 2000;Ichinose and Lukasiewicz, 2002).…”
Section: Role Of Bipolar Cell Sodium Channels In Retinal Processingsupporting
confidence: 92%
“…The dynamic range was also narrower for this class of ganglion cell, and their responses to increments of illumination were larger than ganglion cells receiving TTX-insensitive input. This is in agreement with previous studies that have shown that the dynamic range of transient ganglion cells is narrower than that of sustained ganglion cells (Werblin and Copenhagen, 1974;Thibos and Werblin, 1978). The dynamic range of bipolar and ganglion cell responses to light has been attributed to GABA-mediated input from amacrine cells (Euler and Masland, 2000;Ichinose and Lukasiewicz, 2002).…”
Section: Role Of Bipolar Cell Sodium Channels In Retinal Processingsupporting
confidence: 92%
“…These earlier experiments, however, were performed with all lateral inhibitory mechanisms intact, while the present data were obtained with glycine and GABAA receptor-mediated inhibition blocked. Intensity spans measured here in ganglion cells matched well those reported by Thibos & Werblin (1978) for bipolar cells (2-1 log units), consistent with the idea that the major influence of inhibition on response range may occur at the level of the inner plexiform layer (Werblin & Copenhagen, 1974). This notion remains to be tested.…”
Section: Methodssupporting
confidence: 87%
“…Since inputs from glycinergic amacrine cells apparently tend to be antagonistic to the photoreceptor inputs, it is possible that they contribute to the surround antagonism observed in bipolar cells. This might particularly be the case for antagonism generated by surround transients, since amacrine cells are thought to mediate such antagonism at the inner plexiform layer (Werblin & Copenhagen, 1974). At the same time, our finding that the inputs from glycinergic interplexiform cells are synergistic with the photoreceptor inputs to on-centre bipolar cells suggests that glycinergic interplexiform cells are probably not involved in the generation of surround antagonism, at least for on-centre bipolar cells.…”
Section: Discussionmentioning
confidence: 81%